2015
DOI: 10.12693/aphyspola.128.762
|View full text |Cite
|
Sign up to set email alerts
|

Twinning Evolution as a Function of Loading Direction in Magnesium

Abstract: The twinning activity in random textured cast magnesium during monotonic, room temperature tension and compression tests was monitored by neutron diraction. Decrease of integrated intensity which characterizes the twinned volume fraction of selected reections was compared to its Schmid factor. The comparison shows that twinned fraction correlates with the maximum value of the Schmid factor with high precision during tensile test and with the average value of the Schmid factor during compression test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Grain preferential orientation of wrought magnesium and its alloys has been reported by many studies, since it can influence the mechanical properties and corrosion behavior, as well as many other material characteristics . In fact, in an extruded bar, a large fraction of grains oriented roughly perpendicularly to the extrusion direction has been reported, whereas in an extruded plate basal planes are inclined about 45° to the transverse direction .…”
Section: Resultsmentioning
confidence: 97%
“…Grain preferential orientation of wrought magnesium and its alloys has been reported by many studies, since it can influence the mechanical properties and corrosion behavior, as well as many other material characteristics . In fact, in an extruded bar, a large fraction of grains oriented roughly perpendicularly to the extrusion direction has been reported, whereas in an extruded plate basal planes are inclined about 45° to the transverse direction .…”
Section: Resultsmentioning
confidence: 97%
“…The experimental data presented in Fig. 1 reported for different materials for high manganese austenitic TWIP steels ([59, 60] (a), Titanium [61] and Zirconium [62] (b), Mg and its alloys [63][64][65][66] (c), and a low stacking fault Cu-33Ni alloy [67] and high entropy CoCrFeMnNi alloy [68,69] (d) -see the cited papers for experimental details) are matched by the proposed model, Eq. ( 7), very well.…”
Section: Model Validation and Discussionmentioning
confidence: 55%
“…Čapek et al observed that even a very small strain of 0.1% in Mg can lead to a formation of twins. [ 31 ] In other words, the twins observed in the LPBF Mg foam are formed due to thermal stress caused by rapid solidification. However, there is a need to conduct additional studies to identify the formation mechanism of twin‐like microstructures resulting from solidification.…”
Section: Resultsmentioning
confidence: 99%